Pollen of Pterocarya (Juglandaceae) representatives from natural habitats and St. Petersburg environments - O. A. Gavrilova; G. A. Firsov; D. A. Gornov; A. N. Semenov; A. V. Volchanskaya (Труды по прикладной ботанике, генетике и селекции)
Background. Comparative palynomorphological studies of naturally occurring and introduced Pterocarya Kunth representatives reveal the taxonomic significance of pollen morphological features and pollen characters of cultivated plants. The quality of pollen material and the potential of the plants from the Botanical Garden of BIN RAS for introduction are characterized.Materials and methods. Pollen grains were investigated using light, confocal laser scanning and scanning electron microscopes. Fertility was assessed using the standard acetocarmine method.Results. Comparison of pollen morphology in cultivated and naturally growing plants of this genus was made for the first time. Pollen fertility of two cultivated species (Pterocarya rhoifolia Siebold et Zucc., and P. stenoptera DC.) was very high, generally over 90%. Fertility of P. fraxinifolia (Lam.) Spach grains varied from 28 to 73% in different years, which is a low or medium level of pollen quality. Morphologically, pollen grains of all 12 specimens from five taxa are flattened, medium sized, 21–45 μm in diameter, with 4–8 pores; pores are located mainly at or near the equator. The pores are round or oval, with a limbus. Exine is three-layered, thickened near the pore. The sculpture is microechinate. The low-fertile P. fraxinifolia specimen contains small pollen grains, as well as grains in tetrads and dyads. The data on the introduction of the genus in St. Petersburg are presented.Conclusion. The palynonomophological description is diagnostic for the genus Pterocarya. The Pterocarya pollen is well distinguishable from other wind-pollinated taxa; however, species identification by pollen for spore-pollen analysis is not practicable. Morphologically, the most diverse are the grains of the low fertile specimen P. fraxinifolia. The limited possibility of seed propagation of P. fraxinifolia is probably explained by low pollen fertility. The pollen quality of the introduced P. rhoifolia and P. stenoptera is high.